Dietary spices protect against hydrogen peroxide-induced DNA damage and inhibit nicotine-induced cancer cell migration - Jayakumar, R.; Kanthimathi, M.S. (2012)
Spices are rich sources of antioxidants due to the presence of phenols and flavonoids. In this study, the DNA protecting activity and inhibition of nicotine-induced cancer cell migration of 9 spices were analysed. Murine fibroblasts (3T3-L1) and human breast cancer (MCF-7) cells were pre-treated with spice extracts and then exposed to H 2O 2 and nicotine. The comet assay was used to analyse the DNA damage. Among the 9 spices, ginger, at 50 Î¼g/ml protected against 68 of DNA damage in 3T3-L1 cells. Caraway, cumin and fennel showed statistically significant (p < 0.05) DNA protecting activity. Treatment of MCF-7 cells with nicotine induced cell migration, whereas pre-treatment with spices reduced this migration. Pepper, long pepper and ginger exhibited a high rate of inhibition of cell migration. The results of this study prove that spices protect DNA and inhibit cancer cell migration. Â© 2012 Elsevier Ltd. All rights reserved.